PENGARUH BUDAYA ORGANISASI DAN PENILAIAN PRESTASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SUKA FAJAR PEKANBARU - Afriani "; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at PT Suka Fajar Pekanbaru with a problem in the study is the low performance of employees. The purpose of this study is to determine and analyze the influence of organizational culture and performance appraisal on employee performance partially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 133 respondents to employees of PT Suka Fajar Pekanbaru. The data is then processed using descriptive analysis and quantitative analysis using SPSS by conducting validity, reliability testing, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing by t (partial) and F (simultaneous) testing. The results showed that the first hypothesis testing which is organizational culture on employee performance was tcount (15.037)> ttable (1.978), meaning that organizational culture significantly influenced employee performance. Second performance appraisal of employee performance is tcount (8.698)> ttable (1.978), meaning that performance appraisal has a significant effect on employee performance. The results of Fcount (125,590)> Ftable (3,07) means that organizational culture and performance appraisal have a significant effect on employee performance. Keywords: Organizational Culture, Performance Appraisal, Employee Performance